Urolabida graziae, new urostylidid species from the Philippines with comments on the current taxonomy and systematics of the family (Hemiptera: Heteroptera: Urostylididae) - Roca-Cusachs, Marcos; Paris, Mercedes; Mohagan, Alma; Jung, Sunghoon (Zootaxa, 2021)
A new species of Urostylididae from the Philippine islands (Mindanao) is herein described. This new species, similar to Urolabida bipunctata Stål, 1871, differs from the latter in the shape of the external male genitalia. Urolabida bipunctata and the new species, Urolabida graziae Roca-Cusachs, sp. nov., are extremely similar in external appearance, and fit into the (incomplete) description of genus Urolabida Westwood, 1837. The examination and comparison with the type specimens of other Urostylididae species, especially the male genital capsule, clearly separates this two species from Urolabida tenera Westwood, 1837, the type species of the genus Urolabida, however the taxonomy of this group is not resolved and needs a deep revision, therefore we refrain from description of a new genus-group taxon here. Additionally, images of the type specimens of Urolabida tenera, Urostylis histrionica Westwood, 1837, and Urostylis punctigera Westwood, 1837, are provided and discussion on the current systematics and classification of the family, and particularly of genus Urolabida are also given.